Analisis Strategi Pemasaran Dalam Mempertahankan Loyalitas Pelanggan Pada Merek Mcd Kota Serang - Yuana Putri Febriyanti; Ade Muhita; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
This research aims to determine marketing strategies in maintaining customer loyalty. This research was conducted on the McDonald's trademark in Serang-Banten City. This research method uses qualitative, sampling techniques using random sampling techniques with the process of distributing questions carried out online and to the public as many as 66 respondents who filled in the questions. Based on the research results, it shows that there are still many respondents who often visit local competitors due to the difference in price and taste quality which is not much different. This is directly realized by the McDonald's trademark in Serang-Banten City which is experiencing competition so that the business strategy implemented by McDonald's utilizes its capabilities with strategic management to run advertising, service, public relations and direct marketing campaigns as well as analyzing SWOT with the aim of being able to maintain the trademark. The research results show that McDonald's has a good marketing strategy in maintaining customer loyalty.